Efficacy of Phytoextracts on Macrophomina Phaseolina (Tassi) Goid Causing Leaf Blight of Green Gram - D.H.TANDEL; A.N.SABALPARA; J.R. PANDYA (International Journal of Pharma and Bio Sciences, 2010)
The phytoextracts of eleven plant species evaluated in vitro against M. phaseolina revealed that the extract of onion bulb produced maximum inhibition (98.14%) followed by extract of acacia, ginger, neem, garlic and karanj. The sclerotial formation was also not taken place in all these phytoextracts.